An Owen-Type Value for Games with Two-Level Communication Structures - Rene van den Brink; Anna Khmelnitskaya; Gerard van der Laan (Tinbergen Institute, 2011)
We introduce an Owen-type value for games with two-level communication structures, being structures where the players are partitioned into a coalition structure such that there exists restricted communication between as well as within the a priori unions of the coalition structure. Both types of communication restrictions are modeled by an undirected communication graph, so there is a communication graph between the unions of the coalition structure as well as a communication graph on the players in every union. We also show that, for particular two-level communication structures, the Owen value and the Aumann-Dreze value for games with coalition structures, the Myerson value for communication graph games and the equal surplus division solution appear as special cases of this new value.
Keywords: C71; 330; TU game; coalition structure; communication graph; Owen value; Myerson value